Model Pembelajaran Kooperatif Tipe Jigsaw Untuk Meningkatkan Kemampuan Nyurat Aksara Bali Siswa Kelas X.1 SMA Negeri 6 Denpasar Tahun Ajaran 2022/2023 - Noviana Dewi, Komang Candra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
This consider talks about around (1) the jigsaw sort agreeable learning show to progress the capacity to type in Balinese script for lesson X.1 understudies of SMA Negeri 6 Denpasar within the scholarly year 2022/2023. In analyzing the over issues, Constructivism hypothesis and behaviorism learning hypothesis are utilized. The subjects of this consider were understudies of course X.1 SMA Negeri 6 Denpasar. The strategy utilized to gather information is the perception strategy and the test strategy. The investigate strategy utilized is the Classroom Activity Investigate (CAR) strategy with introductory perception, arranging, activity, activity execution, activity perception or assessment, and reflection, presented with subjective graphic. The comes about of the ponder appeared (1) the jigsaw sort agreeable learning show in learning Balinese script where understudies were separated into bunches, to be specific to begin with being the domestic gather, from the domestic bunch at that point being selected again to gotten to be the master gather. (2) within the first cycle the understudy movement was 8.87 and it expanded within the moment cycle to 10.76 and understudies were classified as very dynamic. (3) the normal understudy learning results within to the begin with cycle was 76.05 with 77.56% classical completeness and expanded within the second cycle with an normal of 82.97 with 94.18% classical completeness. From the investigation it can be concluded (1) the jigsaw sort agreeable learning show on Balinese script fabric has succeeded in expanding understudy learning activity. (2) the jigsaw sort agreeable learning demonstrate on Balinese script fabric succeeded in expanding understudy learning results